Phytochemical Screening And Activity Test of Maja Fruit Extract (Aegle Marmelos L.) on Growth Salmonella typhi and Vibrio cholerae - Yusuf, Nur Annah Achriana; Rannah, St.; Salasa, Alfrida Monica (Journal Microbiology Science, 2023)
Maja fruit (Aegle marmelos L.) contains secondary metabolites that have antibacterial activity in the form of steroids, flavonoids and saponins, which are not used optimally. The target of this study was to observe the antibacterial activity of Maja fruit (Aegle armelos L.) extract on Vibrio cholera and Salmonella typhi. The extraction method formed by maceration and using 96% ethanol solution then the antibacterial activity was tested on the agar diffusion technique. The results of the study show that the range of inhibition zone diameter (mm) is gradual for the Maja Fruit (Aegle marmelos L.) extract test at concentrations of 2%, 4%, 8%. For Salmonella typhi was 13 mm;16,3 mm;19 mm but ciprofloxacin as a positive control was 57mm and DMSO as a negative control did not show any inhibition zone. However, the diameter of the inhibition zone in Vibrio cholera was found to be in the range of 13 mm;18.3 mm;19.6 mm and the positive control ciprofloxacin was 32.3 mm , but the negative control did not have an inhibiting zone. The results of statistical tests showed that Maja fruit (Aegle marmelos L.)  extract had antibacterial activity on Vibrio cholerae and Salmonella typhi at the maximum concentration of 2% w/v (P <0.05).